Characterisation of Luminescent Downshifting Layer effects on Silicon Solar Cells - Mc Cormack, Sarah; Sethi, Arunima; Chandra, Subhash; Cass, Bill (My University, 2021)
This paper presents the effects of the characteristics of a polymer layer applied to a silicon based dual connection solar cell. The characteristics of the polymer solution of which is used as the base of a Luminescent Downshifting (LDS) layer before the addition of a dye. This layer aids in the shifting of the wavelength of light from a range that is not effectively used. The LDS has a large affect upon the solar cells improvement when applied correctly. The characteristics of the LDS layer were tested in this investigation along with the affects of different dyes, the thickness of the layer that is applied to the cell and the consistent quality of the layer before, during and after application. . The ability to absorb light, fragility of the layer and the application of the layer are affected by these changes. From the implementation of the LDS layers, it can be shown that the variation in the characteristics can have an impact on the solar cell’s performance.
World Renewable Energy Congress
PUBLISHED
Keywords: Photovoltaics; Luminescent Downshifting Layer; Polymer layer